SPECTROPHOTOMETRIC DETERMINATION OF DRUGS USING CHLORAMINE-T AND RHODAMINE-B DYE - BADDENAPALLI TIRUPATHI; GANDU VENKATESHWARLU (International Journal of Pharma and Bio Sciences, 2015)
Simple, sensitive and selective methods are developed for the spectrophotometric determination of drugs, viz., Gemifloxacin mesylate, Moxifloxacin hydrochloride, Sumatriptan succinate, Phenylephrine hydrochloride and Duloxetine hydrochloride. The methods use Chloramine-T oxidant and Rhodamine-B dye as reagents and are based on adding of a known excess of Chloramine-T to drugs in hydrochloric acid medium followed by determination of residual oxidant by reacting with a fixed amount of Rhodamine- B and measuring the absorbance at 557 nm. These methods have been applied for the determination of drugs in their pure form as well as in tablet formulations. The methods have been validated in terms of guidelines of ICH.